FRI0518 Epidemiology of rheumatoid arthritis in a universal public health care system: results from the ontario ra administrative database (ORAD). (23rd January 2014) - Widdifield, J.; Paterson, J. M.; Bernatsky, S.; Tu, K.; Thorne, J. C.; Bombardier, C.
Abstract : Background: Valid population-based assessments of sufficiently large populations are required to obtain robust estimates, particularly when exploring the influence of various factors (age, sex, time, and geographic area). Objectives: To describe the epidemiology of RA over the past 15 years in Ontario, Canada's most populous province. Methods: We used ORAD, a population-based research cohort of all Ontarians with RA that was generated from administrative databases over the period 1991-present using a validated case definition. Patients are included in ORAD if they are admitted to a hospital with a RA diagnosis or have ≥ 3 RA diagnosis codes over 2 years, with ≥ 1 provided by a specialist. This case definition yielded a 78% sensitivity, 100% specificity and 78% PPV based on medical record reviews. Once all criteria are met, incidence is defined as the first medical encounter for RA. ORAD records were linked with census data to calculate crude and age/sex-standardized rates among men and women, and by age group over 1996-2010. Results are reported from 1996 onwards to allow for sufficient time to identify prior prevalent cases ("run-in period" to distinguish between incident and prevalent cases), and up until 2010 to allow for a 2-yr "look forward" period to meet the terms of the case definition. Sensitivity analyses were performed to assess the impact upon incidence and prevalence of varying the length of the run-in/case ascertainment period (yrs of data). Results: As of 2010, there were 97, 499 Ontarians identified with RA, corresponding to a cumulative prevalence over 1991-2010 of 0.9% (females 1.3%, males 0.5%). Prevalence increased steadily with age: 15-24y (0.1%), 25-34y (0.2%), 35-44y (0.5%), 45-54y (0.9%), 55-64y (1.5%), 65-74y (2.1%), 75-84 (2.6%) to ≥85y (2.7%) as of 2010. Age/sex-standardized prevalence increased steadily from 473 cases per 100, 000 population (0.5%) in 1996 to 784 cases per 100, 000 (0.9%) in 2010 (which had more years of observation time than 1996). Prevalence was also higher in northern rural communities (1.0%) than in southern urban areas (0.7%). Age/sex-standardized incidence ranged from 62 cases per 100, 000 in 1996 to 54 cases per 100, 000 in 2010. Sensitivity analyses showed that using 5, 10 and 15 yrs of data (run-in period), the incidence in 2010 was 58, 55, and 54 (per 100, 000), respectively. By increasing the case ascertainment period over 5, 10 and 15 years of data, the prevalence estimates in 2010 varied from 555, 664, and 748 (per 100, 000), respectively. Conclusions: Prevalence increased with age, was highest among females and rural communities. There was an increase in prevalence over time; however, increasing the case ascertainment period from 5 to 15 years increased the cumulative prevalence by 36%. Thus, factors contributing to the apparent increase in prevalence over time may be attributed to the increasing time to ascertain cases (which may be latent in the population during earlier years of study), increasing survival and/or an increase in the aging background population. Incidence may be declining over time; however, increasing the observation period to distinguish between incident and prevalent cases has an effect in decreasing incidence as fewer prevalent cases are misclassified as incident over time. Disclosure of Interest: None Declared